2015
DOI: 10.1063/1.4922369
|View full text |Cite
|
Sign up to set email alerts
|

Novel comparison of microscopy and diffraction techniques on the structure of iron oxide nanoparticle monolayers transferred by Langmuir-Schaefer method

Abstract: Iron oxide nanoparticles undergo self-assembly into well-ordered monolayer films of macroscopic size at the air-water interface. This self-assembly process is the result of the van der Waals forces between the constituent particles. For roughly spherical particles, this monolayer is a 2D hexagonal close packed lattice. With Grazing Incidence X-Ray Diffraction (GID), one can obtain global statistical information about the film's spacing and correlation length. Herein, we demonstrate that comparable structural i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Second-order intensity autocorrelation functions were calculated using XPCSGUI software designed for sector 8-ID at APS. [22]. Both methods yielded the same center-to-center particle spacing, and correlation length of about 15 particle separations [23].…”
Section: Experimental Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Second-order intensity autocorrelation functions were calculated using XPCSGUI software designed for sector 8-ID at APS. [22]. Both methods yielded the same center-to-center particle spacing, and correlation length of about 15 particle separations [23].…”
Section: Experimental Methodsmentioning
confidence: 85%
“…Recently, great attention has been paid to the structure, ordering, and variety of elastic responses of thin sheets of nanoparticles at the air-water interface in a Langmuir trough [4,5,17,[19][20][21][22][23][24][25][26][27][28]. Upon drop-casting onto the surface of water, monodisperse nanoparticles (<10% polydispersity) self-assemble into islands of two-dimensional (2D) hexagonally close packed crystalline domains surrounded by large voids.…”
Section: Introductionmentioning
confidence: 99%
“…The difference can be caused by several factors, including imbalance of repulsive and attractive forces [20], the transfer method [23] and physical properties of the particles [24]. Furthermore, an average structural domain size as obtained by GISAXS and SEM can have different values due to the difference in resolution and due to different areas of a sample probed by these techniques [25].…”
Section: Introductionmentioning
confidence: 99%
“…Although electron microscopy was not used in this study, Stanley et al 24 reported that the structural information for both the unit cell and domain sizes, determined from in situ X-ray scattering of an NP Langmuir monolayer, is within the experimental precision, equivalent to that determined from the analysis of the SEM images obtained from the same monolayer transferred to a solid substrate. This previous study demonstrated that the packing of the NPs at the air−water interface is reasonably homogeneous over hundreds of mm 2 sampled by X-rays.…”
Section: Resultsmentioning
confidence: 88%